Okulöncesi Eğitimde Çevre Gezilerinin Ulaşım Süreçleri Açısından Değerlendirilmesi - Şahin, Belkıs Ece; DOSTOĞLU, NESLİHAN (My University, 2016)
Günümüz kentlerinde yaşanan trafik, güvenlik sorunları ve oyun alanlarının yetersizliği gibi nedenler çocukları dış mekanlardan uzaklaştırmaktadır. Bu ortamda, okullardan sorumluluk üstlenerek çocukların fiziksel çevreleriyle olan ilişkisini güçlendirmesi beklenmektedir. Bu çalışmada çocukların okul dışına çıktığı gezilerdeki ulaşım süreçlerinin çocuk, öğretmen ve veli açısından nasıl değerlendirildiği incelenmektedir. Bursa’da üç bağımsız anaokulunda, 5 yaş grubundan eşit sayıda kız ve erkek olmak üzere 30 çocuk, velileri ve öğretmenleriyle yapılan birebir görüşmelerde gezilerde yaya ve araç ulaşımının eşit düzeyde tercih edildiği ve çocukların ulaşım süreçlerini çevreyle iletişim, sağlıklı gelişim ve sosyalleşme yönünden katkı sağlayan deneyimler olarak değerlendirdikleri görülmüştür. Veliler ve öğretmenler tarafından okul dışı deneyimlerin çocuklar üzerindeki olumlu katkısına dikkat çekilmiş ve yeterli sayıda gezi düzenlenememesi eleştirilmiştir. 4 Okulöncesi dönemde çocukların yaşadıkları çevreyi tanıması ve farklı deneyimlerle karşılaşmasını sağlayacak gezilerin desteklenmesi için öncelikle, okulöncesi yaş grubundaki çocukların algı ve davranışları dikkate alınarak, kentlerde çocuklar için ulaşımın güvenli hale getirilmesine önem verilmelidir.

Motor vehicle traffic, safety and security issues and insufficiency of playgrounds in contemporary cities keep children away from outdoors. Under these circumstances, schools are expected to assume responsibility with a view to strengthening the relationship of children with their physical environment. In this study, aims at supporting tours allowing preschool children to interact with their environment and children’s, teacher’s and parent’s preferences and evaluations about environment tours are provided. Interviews with 30 children in the age group of 5 years, from three different nurseries, their parents and teachers have revealed that pedestrian and motor vehicle transportation are equally preferred and that they are considered as experiences contributing to transportation processes of children with respect to communication with the environment, healthy growth and socializing. Both parents and teachers have emphasized the positive contribution of extra scholastic experience to the children and complained that the number of tours organized for that purpose is not sufficient5 . Safe and secure transportation facilities for preschool children in cities must be provided with a view to increasing the number of tours enabling the children to learn about their environment and to experience the life. To this end, perceptions and behaviors of preschool children as well as their opinions and recommendations must be taken into consideration and in researches aiming at improvement of urban living conditions.
An Evaluation on Environment Tours in Preschool Education About Transportation Processes
Keywords: Okulöncesi Eğitim; Fiziksel Çevre; Dış Mekan; Ulaşım; Preschool Education; Physical Environment; Outdoor; Transportation